Vegetation of the Angmagssalik District, Southeast Greenland. III. Epilithic Macrolichen Communities. - Daniëls, F. J. A. (Meddelelser om Grønland, 1975)
The epilithic macrolichen vegetation in the Angmagssalik District was studied in connection with phytosociological investigations. Based upon 32 vegetation analyses 5 vegetation units are distinguished according to the concepts of the French-Swiss School of Phytosociology: 1. the Alectoria pubescens sociation soc. nov., 2. the Umbilicarietum cylindricae, 3. the Parmelietum omphalodis sphaerophoretosum fragilis subass. nov., 4. the Umbilicarietum arcticae and 5. the community of Xanthoria elegans. Although the substrate in this case is not such an important ecological factor, a distinct relation with the habitat could be proved. Studies of the literature showed that phytosociological knowledge of epilithic lichens in Greenland and in other arctic and northern alpine areas is very scant.